Photopic and Mesopic Contrast Sensitivity Function in the Presence of Glare and the Effect of Filters in Young Healthy Adults - Domínguez-Vicent, Alberto; Helghe, Emma; Wahlberg Ramsay, Marika; Venkataraman, Abinaya Priya (Frontiers in Psychology, 2021)
Purpose: The aim of this study is to evaluate the effect of four different filters on contrast sensitivity under photopic and mesopic conditions with and without glare. Methods: A forced choice algorithm in a Bayesian psychophysical procedure was utilized to evaluate the contrast sensitivity. Five different spatial frequencies were evaluated: 1.5, 3, 6, 12, and 18 cycles per degree (cpd). The measurements were performed under 4 settings: photopic and mesopic luminance with glare and no glare. Two long pass filters (LED light reduction and 511nm filter) and two selective absorption filters (ML41 and emerald filter) and a no filter condition were evaluated. The measurements were performed in 9 young subjects with healthy eyes. Results: For the no filter condition, there was no difference between glare and no glare settings for the photopic contrast sensitivity measurements whereas in the mesopic setting, glare reduced the contrast sensitivity significantly at all spatial frequencies. There was no statistically significant difference between contrast sensitivity measurements obtained with different filters under both photopic conditions and the mesopic glare condition. In the mesopic no glare condition, the contrast sensitivity at 6 cpd with 511, ML41 and emerald filters was significantly reduced compared to no filter condition. Similarly, with these filters the area under the contrast sensitivity function in the mesopic no glare condition was also reduced. A significant positive correlation was seen between the filter light transmission and the average AULCSF in the mesopic non glare condition. Conclusion: The contrast sensitivity measured with the filters was not significantly different than the no filter condition in photopic glare and no glare setting as well as in mesopic glare setting. In mesopic setting with no glare, filters reduced contrast sensitivity.